Live-Attenuated Respiratory Syncytial Virus Vaccine Candidate With Deletion of RNA Synthesis Regulatory Protein M2-2 is Highly Immunogenic in Children. (2nd March 2018) - McFarland, Elizabeth J; Karron, Ruth A; Muresan, Petronella; Cunningham, Coleen K; Valentine, Megan E; Perlowski, Charlotte; Thumar, Bhagvanji; Gnanashanmugam, Devasena; Siberry, George K; Schappell, Elizabeth; Barr, Emily; Rexroad, Vivian; et al.
Abstract: Background: Live respiratory syncytial virus (RSV) candidate vaccine LIDΔM2-2 is attenuated by deletion of the RSV RNA regulatory protein M2-2, resulting in upregulated viral gene transcription and antigen expression but reduced RNA replication. Methods: RSV-seronegative children ages 6–24 months received a single intranasal dose of 10 5 plaque forming units (PFU) of LIDΔM2-2 (n = 20) or placebo (n = 9) (NCT02237209, NCT02040831). RSV serum antibodies, vaccine infectivity, and reactogenicity were assessed. During the following RSV season, participants were monitored for respiratory illness and pre- and post-RSV season serum antibodies. Results: Vaccine virus was shed by 95% of vaccinees (median peak titers of 3.8 log10 PFU/mL by quantitative culture and 6.3 log10 copies/mL by PCR); 90% had ≥4-fold rise in serum neutralizing antibodies. Respiratory symptoms and fever were common in vaccine (95%) and placebo (78%). One vaccinee had grade 2 rhonchi concurrent with vaccine shedding, rhinovirus, and enterovirus. Eight of 19 vaccinees versus 2 of 9 placebo recipients had substantially increased RSV antibody titers after the RSV season without medically attended RSV disease, indicating anamnestic vaccine responses to wild-type RSV without significant illness. Conclusion: LIDΔM2-2 had excellent infectivity and immunogenicity, encouraging further study of vaccine candidates attenuated by M2-2 deletion. Clinical Trials Registration: NCT02237209, NCT02040831. Abstract : The live respiratory syncytial virus (RSV) vaccine LIDΔM2-2, attenuated by deletion of the RNA regulatory protein M2-2, had excellent infectivity and immunogenicity in RSV seronegative 6–24-month old children, encouraging further study of vaccine candidates attenuated by M2-2 deletion.